Enhancing Phosphorous Recovery in a Novel Biofilter System - 孙健 田晴 李方 王凤蕊 杨波 (东华大学学报（英文版）, 2013)
Developing new techniques to remove and recover phosphorous simultaneously from wastewaters is very important for sustainable utilization of phosphorous resource and prevention of eutrophication. The feasibility of phosphorus bioaccumulation in a novel continuous alternating anaerobic /aerobic biofilter and benefits of such accumulation for its further recovery as magnesium ammonia phosphate （MAP） were studied. The system was operated for seven months and employed the atomic absorption spectrophotometer （AAS） method to analyze the distribution change of magnesium and calcium with phosphate in the biofilter during that period. The benefits of utilizing the biofilter system to accumulate phosphorous ＆ magnesium and suppress calcium simultaneously to phosphorous recovery as MAP were explained with the aid of chemical equilibrium models. The improved phosphorus recovery from 42% to 82% was approved in the recovery experiments and the recovery products mainly as MAP were evidenced and characterized with scanning electron microscopy （SEM） . The study provides references for designing and operating the novel alternating anaerobic /aerobic biofilter for phosphorus bioaccumulation and recovery.